2015
DOI: 10.1007/s11605-015-2801-8
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Abdominal Syndrome Due to Nervous Compression. Study of 100 Cases and Proposed Diagnostic-Therapeutic Algorithm

Abstract: ObjectiveIn the medical literature, thoracic disc protrusion has traditionally been considered a rare occurrence. We hypothesise that the incidence of such protrusions and their abdominal symptoms is higher than is generally believed and that their presence may account for a significant proportion of chronic non-visceral abdominal pains. Accordingly, the present study was designed to identify and quantify the symptoms experienced by patients with thoracic disc protrusion and to assess the relative risk of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…This higher rate than in the study by Wood et al may be due to our inclusion of medium-sized and small hernias. As reported previously, [10,11,15] smaller hernias are also capable of generating important symptoms.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This higher rate than in the study by Wood et al may be due to our inclusion of medium-sized and small hernias. As reported previously, [10,11,15] smaller hernias are also capable of generating important symptoms.…”
Section: Discussionsupporting
confidence: 77%
“…[14] High-resolution magnetic resonance (HRMN) imaging has increased the frequency of radiological diagnosis of HDT. In a previous study, [15] we reported that the frequency of this pathology is quite significant, and when we interviewed the patients affected, practically all of them were found to be symptomatic.…”
Section: Discussionmentioning
confidence: 80%
“…2 The diagnostic yield of nerve conduction studies and electromyography has not been evaluated, but they might play a role in certain dubious cases, supporting a relationship between radiologic findings and symptoms, because thoracic disc protrusions occur in >11% of adults. 3 Important clues in this case were the radiation to the back, which appears in >90% of subjects with abdominal wall pain owing to thoracic disc protrusion, and the worsening induced by spinal movements, present in >50%. 3 Initial management includes conventional analgesia, calcium a 2-d ligands and tricyclic antidepressants.…”
mentioning
confidence: 82%
“…3 Important clues in this case were the radiation to the back, which appears in >90% of subjects with abdominal wall pain owing to thoracic disc protrusion, and the worsening induced by spinal movements, present in >50%. 3 Initial management includes conventional analgesia, calcium a 2-d ligands and tricyclic antidepressants. Infiltration of the metamere wall, topical 5% lidocaine patches and opioid agonists might be used in more severe cases.…”
mentioning
confidence: 82%
See 1 more Smart Citation